Effectiveness of Quality Assessment in Construction Project - Mohd Nasrun Mohd Nawi; Nisamini Subramaniam; Roshartini Omar; Norliana Sarpin (International Journal of Supply Chain Management, 2019)
Malaysia is one of the countries which is growing rapidly and show a great result in construction. In real terms, the Malaysian construction industry registered positive growth, supported by large-scale investments under the government’s 10th Malaysia Plan. The growth of construction industry increases the perception of client on Malaysia projects. In current scenario, client have a high level of awareness on quality of outcome. The higher the quality achieved in building projects ensure the marketability and enhance of clients. As such construction projects that are able to be completed with distinctive quality will definitely enable to delight their customers. Thus, this study aims to identify the lacking in quality assessment as a strategy to improve quality of residential project. Therefore, objective of this study is to investigate the implementation of construction quality assessment in reducing number of defects in construction projects. Apart from that, this study conducted to investigate the limitation of construction quality assessment in reducing number of defects in residential projects. This study also conducted to develop a framework of construction quality assessment towards reducing number of defects in residential projects. The conceptual framework consists of major component that show lack of quality assessment and improvements in quality assessment. The finding shows that, there are lacking in quality assessment which affect the quality of construction project. Thus, this framework will be an effective strategy to improve the performance level of construction quality assessment.